A drug utilisation study of antidepressants in children and adolescents using the General Practice Research Database. Issue 12 (19th November 2004) - Murray, M L; de Vries, C S; Wong, I C K
Abstract : Aims: To characterise prescribing patterns of antidepressants (ATDs) to children and adolescents aged ⩽18 years in the UK. Methods: Subjects issued at least one ATD prescription between 1 January 1992 and 31 December 2001 were identified from the UK General Practice Research Database. Prescribing patterns, annual prevalence, morbidity patterns, and time to discontinuation of ATD use were identified. Results: A total of 24 976 subjects received 93 091 prescriptions; 51 868 (55.7%), 38 429 (41.3%), and 2708 (2.9%) prescriptions were for tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), and other ATDs respectively. ATD prevalence increased 1.7-fold from 1992 to 2001. TCA prevalence decreased by 30% from 3.6 to 2.5 per 1, 000; SSRI prevalence increased 10 times from 0.5 to 4.6 per 1, 000. In new ATD users aged ⩽10 years, the most common diagnosis associated with TCA use was nocturnal enuresis (75.1%); in those aged ⩾15 years, it was depression (45.8%). Depression was also associated with SSRI use (69.0%). For new users with depression, the median treatment durations for TCAs and SSRIs were 30 and 58 days respectively. TCA users were more likely to terminate treatment than SSRI users (TCAs v fluoxetine: 1.40, 95% CI 1.32 to 1.47; non-fluoxetine SSRIs v fluoxetine: 1.01, 95% CI 0.96 to 1.07). Conclusions: SSRIs have gained popularity for the treatment of depression compared with TCAs. TCAs are still used despite their lack of efficacy in prepubertal depression and their moderate effect in adolescents. However, >50% of subjects discontinue treatment after two months, with TCA users stopping earlier than SSRI users.